Ethnographic film and the teaching of African music: a technological approach of representing past musical hegemonies - Matiure, Perminus; Shoko, T. (Midlands State University, 2014)
Teaching African music in schools has not yet received adequate attention from curriculum planners in respect of the involvement of ethnographic film as a pedagogy of teaching music. Film as an aid to teaching and learning attempts to present a learning atmosphere in which music is learned in its performative and contextual state. Students are afforded an opportunity to experience music as it is used by the society to solve cosmological problems. In this article the writer attempts to justify the use of ethnographic film in the teaching of African music to students who have not been exposed to music in the society. The information that supports this article is drawn from the writers personal experiences in the field as he was collecting data for his Master thesis recording audio-visual images. He discovered that film can play a very important role of representing a particular ethnic groups music in its totality. A teacher can bring life to his/her teaching by making use of film. Students can have an opportunity to observe the protagonists performing a particular dance in its performative state. Although expensive, the use of film in teaching indigenous music will go a long way in closing the gap between reality and theory. A lot of teaching content can then be drawn. This article will unpack the different types of content that children can to from one single ethnographic film. The information that furnishes this article was collected through desk research approach as well as face to face interviews with music lectures who teach indigenous music at Midlands State University.